Floristic composition of weeds in different winter and summer covers - Caratti, Fernanda Cassiane; Lamego, Fabiane Pinto; Reinehr, Marcela; Fabiani, Mirian Fracasso; Frizon, Daiane; Mazzon, Marines (Comunicata Scientiae, 2018)
The usage of cover crops is an adopted cultural measure that shows positive effects when associated with the no-till system and weed management. During the cycle of the plants there might be competition within them for water, solar radiation and nutrients and effects of allelopathic substances released by leaching, volatilization and/or root exudation in the environment might also coexist. The study aimed to quantify the floristic composition of weed species in an cultivated area with cover crops during winter and summer, for two years, 2011/12 and 2012/13, in an experimental area of UFSM, Campus of Frederico Westphalen – RS state, Brazil. The treatments consisted of Italian ryegrass, wild radish, black oat, vetch, wheat and uncultivated, in winter, and, sorghum, sunflower, black velvet bean, dwarf velvet bean, gray velvet bean and green velvet bean in the summer. In the first year of the experiment, a diversity of weeds in winter was observed, especially occuring Stellaria media and Bowlesia incana. In summer, the weeds of higher importance were Ipomoea spp. and Bidens spp., both of utter importance in agricultural systems. Winter cover crops of wild radish and Italian ryegrass and summer cover crops of sorghum and sunflower provided a lower weed infestation